Complications of pneumococcal meningitis in a child with Proteus Syndrome: a case report and literature review: Pneumococcal meningitis in a child with Proteus Syndrome - Ostojić, Slavica; Kravljanac, Ruzica; Kovačević, Gordana; Vučetić Tadić, Biljana; Kuzmanović, Miloš; Prijić, Sergej; Gazikalović, Slobodan; Paripović, Aleksandra; Sarajlija, Adrijan (Medical Research, 2024)
Introduction: Proteus syndrome (PS) is a very rare disease characterized by asymmetric overgrowth. Case presentation: We describe the clinical case of a 6.5-year-old girl with Proteus syndrome diagnosed and treated in Mother and Child Health Care Institute of Serbia. At the age of 11 months she was treated for pneumococcal sepsis and meningitis. Disease was complicated by intracranial thromboses of venous sinuses, subdural empyema, brain infarction and severe neurological deficit in the acute phase. Portal and mesenteric venous thromboses were also verified. At the age of 2.5 years echocardiography and cardiac magnetic resonance revealed ascending aortic aneurysm. The patient died suddenly at the age of 6.5 at home. The cause of death was unknown. Conclusion: In conclusion, despite the use of aggressive antibiotic therapy, multiple life-threatening complications of pneumococcal disease have occurred in our patient with PS. Having in mind previously described immune disturbances in patients with PS, we can speculate that immune system of our patient was compromised due to primary diagnosis. Published data related to immunological response in PS patients are insufficient mostly due to the rarity of the disease, so the definitive conclusion regarding the propensity for serious infections requires further studies.